Perdagangan Karbon Hutan Aceh: Analisis Hukum Pada Tahapan Perencanaan - Sanusi Sanusi; Mujibussalim Mujibussalim; Fikri Fikri (Universitas Syiah Kuala, 2013)
ABSTRACT: The Province of Aceh has wide forest area which is potential for forest carbon trade in international market. However, incomplateness of legal bases for carbon trade which is consistant to wide-special Aceh autonomy and sincron and harmonis with Indonesian national law may create abstracles in utilizing that opportunities. This research is aimed at providing input to Government of Aceh in selecting alternative precise legal entities and regulating Aceh forest carbon trade in international market. In this research the combination of normative, comperative, and social-legal research approaches, to answer legal issues as research questions. The finding shows that is utilized proper implementing legal entities for Aceh forest carbon trade in international market is that which can combine various elements and interests of right holders and stakeholders. Combination of government, componies and civil society will strengthen synergicity and strengths in performing activities. Regulating Aceh forest carbon trade can be implemented in form of specific Qanun Aceh or as a part of contents of Qanun Aceh on Forestry and/or in governatorial decree, as implementing regulation which is already directed by related Qanun Aceh. It is recommended to Government of Aceh to increase socialization and participation of right holdels and stakeholders in each process of management and creating relevant legislation and/or regulation. Aceh Forest Carbon Trade: Legal Analysis In The Planning Step